A multiaxial molecular ferroelectric with record high TC designed by intermolecular interaction modulation. Issue 7 (5th January 2021) - Li, Jun-Yi; Xu, Qiu-Ling; Ye, Si-Yu; Tong, Liang; Chen, Xiang; Chen, Li-Zhuang
Abstract : Through precise and ingenious molecular modification, we successfully obtained a multiaxial ferroelectric, [FEtDabco]ZnI3 ( N -fluoroethyl- N ′-ZnI3 -1, 4-diazabicyclo[2.2.2]octonium), with a blindingly high Curie temperature ( T C ) of 540 K, which is promising for applications under extreme thermal conditions. Abstract : Through precise and ingenious molecular modification, we successfully obtained a multiaxial ferroelectric, [FEtDabco]ZnI3 ( N -fluoroethyl- N ′-ZnI3 -1, 4-diazabicyclo[2.2.2]octonium), with a record high T c (540 K) among molecular ferroelectrics, which is promising for application under extreme thermal conditions.